ANALISIS PERBEDAAN ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY SEBELUM DAN SESUDAH PENGUMUMAN KEBIJAKAN LOAN TO VALUE (LTV) BANK INDONESIA (Studi pada Perusahaan Sektor Property, Real Estate and Building Construction yang terdaftar di Bursa Efek Indonesi - Elsafan Kukuh Aditya; Nila Firdausi Nuzula (Jurnal Administrasi Bisnis, 2019)
This research was conducted with the aim to analyse the impact of policy easing Loan To Value 2018 against capital market reaction in Indonesia stock exchange (IDX) especially in the sector of Property, Real Estate and Building Contruction area. This research method using event study by using indicators of abnormal return (AR) and trading volume activity (TVA). The data used are secondary data with a period of observation that is 5 days (July 23,2018 – July 29,2018) before the announcement of the policy of LTV, 1st day (July 30, 2018) when the announcement of the policy and 5 days (July 31,2018 – August 6, 2018) after pemuman policies of LTV. Based on the results of different trials that there are significant differences in average abnormal return stocks of companies in the sector, Property, Real Estate and Building Contruction area in the period surrounding the policy easing LTV. While the test is different to trading volume activity (TVA) shows that there was no significant difference in average trading volume of activity of the company shares in the sector of Property, Real Estate and Building Contruction area in the period surrounding the LTV policy easing. Keywords: Event Study,  Loan To Value Policy, Abnormal Return, Trading Volume Activity. АBSTRАK Penelitian ini dilakukan dengan tujuan untuk menganalisis dampak pelonggaran kebijakan Loan To Value 2018 terhadap reaksi pasar modal di Bursa Efek Indonesia (BEI) khususnya pada sektor Property, Real Estate and Building Contruction. Penelitian ini menggunakan metode event study dengan menggunakan indikator abnormal return (AR) dan trading volume activity (TVA). Data yang digunakan adalah data sekunder dengan periode pengamatan yaitu 5 hari (23 Juli 2018 – 29 Juli 2018) sebelum pengumuman kebijakan LTV, 1 hari (30 Juli 2018) saat pengumuman kebijakan dan 5 hari (31 Juli 2018 – 6 Agustus 2018) setelah pemuman kebijakan LTV. Berdasarkan hasil uji beda bahwa terdapat perbedaan yang signifikan rata-rata abnormal return saham-saham perusahaan pada sektor Property, Real Estate and Building Contruction pada periode seputar pelonggaran kebijakan LTV. Sedangkan uji beda untuk trading volume activity (TVA) menunjukkan bahwa tidak terdapat perbedaan yang signifikan rata-rata trading volume activity saham-saham perusahaan pada sektor Property, Real Estate and Building Contruction pada periode seputar pelonggaran kebijakan LTV. Kata Kunci: Event Study, Kebijakan Loan To Value, Abnormal Return, Trading Volume Activity.